A comparison of cupping and descriptive sensory analysis of Colombian brewed coffee - Di Donfrancesco, Brizio; Guzman, N. Gutierrez; Chambers, Edgar, IV (My University, 2014)
Sensory profiles of thirteen coffee samples from the Huila Region, Colombia, were evaluated using two different sensory panels, a highly trained descriptive sensory panel and a group of certified coffee cuppers. The trained panel consisted of six descriptive panelists who developed a lexicon to evaluate and then test the coffee samples. Four ‘cuppers’ scored samples based on the Speciality Coffee Association of America “Cupping Protocol”. In addition cuppers generated tasting notes to characterize the different coffee samples. Data analysis indicated little overlap between the two methods and a low relationship between the two different sets of terms. Moreover, tasting notes by cuppers indicate lack of agreements on the terms used to describe samples with only four terms used by more than two assessors to describe a single coffee product, out of a total of 59 terms used by the cuppers. The results indicate that the cupping method provides different information that cannot be used as an alternative to descriptive sensory analysis with trained panelists when describing the sensory profile of coffee products. Results also indicate that further training of cuppers is needed in order to potentially provide higher agreement in generating tasting notes to better characterize coffee samples.
Comparison of results from cupping and descriptive sensory analysis of Colombian brewed coffee
Keywords: Coffee; Sensory analysis; Cupping; Descriptive analysis; Aroma; Flavor